2017
DOI: 10.1145/3050218
|View full text |Cite
|
Sign up to set email alerts
|

Constant-Rate Coding for Multiparty Interactive Communication Is Impossible

Abstract: We study coding schemes for multiparty interactive communication over synchronous networks that suffer from stochastic noise, where each bit is independently flipped with probability ε. We analyze the minimal overhead that must be added by the coding scheme to succeed in performing the computation despite the noise. Our main result is a lower bound on the communication of any noise-resilient protocol over a synchronous star network with n parties (where all parties communicate in every round). Specifically, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Alon et al [ABE + 16] showed that if the topology is a clique, or a dense d-regular graph, then constant rate coding is also possible. Yet, Braverman, Efremenko, Gelles, and Haeupler [BEGH17] proved that a constant rate is impossible if the topology is a star. All the above works assume a synchronous fully-utilized network.…”
Section: Related Workmentioning
confidence: 99%
“…Alon et al [ABE + 16] showed that if the topology is a clique, or a dense d-regular graph, then constant rate coding is also possible. Yet, Braverman, Efremenko, Gelles, and Haeupler [BEGH17] proved that a constant rate is impossible if the topology is a star. All the above works assume a synchronous fully-utilized network.…”
Section: Related Workmentioning
confidence: 99%
“…We devote Section 5 to sketch the proof of the more involved lower bound of Theorem 1.1. Full details can be found in the full version of this manuscript [6]. Below we give a rather intuitive overview of our lower bound result and the techniques we use.…”
Section: Theorem 12 (Upper Bound)mentioning
confidence: 99%